CUSTOMER SATISFACTION IN POSTGRADUATE PROGRAM THROUGH INCREASED PERCEIVED VALUE - Noor Sembiring; Rosmaniar Sembiring (Dinasti Publisher, 2021)
This research is a continuation of previous research conducted by Gaston LeBlanc and Nha nguyen, 1999, a survey of the dimensions that affect the perceived value, and a study conducted by Gordon HG McDougall, Terrence Levesque (2000) regarding the relationship between perceived value and customer satisfaction. It encouraged the author to conduct further research to see the effect of the perceived value dimensions on customer satisfaction, which is applied to universities that the author is managing. This study aims to determine the impact of postgraduate students' assessments on what they feel about the college activities they are undergoing with the satisfaction they feel. and explore the dimensions of perceived value that determine and cause consumers to feel satisfied. Based on the tests that have been carried out, it turns out that from the 6 dimensions, only 4 sizes directly influence customer satisfaction. This is supported by the results of the hypothesis testing of these four dimensions that it has a t-value greater than t table.